Determination of Glycerin from a Marketed Personal Care Product Using Gas Chromatography. (9th February 2015) - De, Amit Kumar; Chowdhury, Partha Pratim; Chattopadhyay, Shyama Prasad
Abstract : The current study presents a packed column gas chromatographic technique for the estimation of glycerin using a flame ionization detector from a marketed hair tonic in presence of resorcinol, ethanol, biotin, keratin hydrolysate, undecylenic acid alkylolamide (hyalkyl HBU), D-biotin, nicotinic acid, and polyvinylpyrrolidone. The validation studies show the proposed method to be specific, sensitive, precise, and accurate. The method is found to be linear in the concentration range 1.25 mg/mL to 10.02 mg/mL with r 2 value 0.99. The limit of detection and the limit of quantitation were 0.01 mg/mL and 0.05 mg/mL, respectively. The method does not involve any complex sample preparation procedure and is therefore suitable for regular analysis of glycerin from marketed hair tonic.